Tool to overcome the managerial dilemma: Decision making or problem solving - Acevedo Borrego, Adolfo (2010)
The current approach to deal with unwanted situations is to make decisions based on concepts and pre-defined paradigms, this “solves” an aspect of the problem, but creates failures in other aspects which become even more serious problems than the original. The resolution of problems is handled in a strategic level, it requires a change of approach to face reality. For this, apply a tool that incorporates in a matrix array for solving complex problems, it is constructed by two Cartesian axes that define four dimensions and four analysis fields. This tool allows analyzed together, the perspective of the decision maker in relation to his environment decision.